FACTORS THAT INFLUENCE ON DIVIDEND POLICY BETWEEN INDONESIA AND CHINA BANKING - Ari Kharisma; Windy Atmawardani Rachman (Jurnal Ilmiah Ekonomi Bisnis, 2018)
This research aimed to investigate influence of stock price, growth, profitability and free cash flow on dividend policy. Dividend is one of the agency problem that occurs because there is separation between the shareholders (as principal) with company management (as agent). In agency theory, agency relationship arises when one or more persons (principal) employs another person (agent) to provide a service and then delegate a decision-making authority to the agency (Jensen and Meckling, 1976). Samples in this research are Indonesia and China banking companies listed on the IDX (Indonesia Stock Exchange) and Shanghai Stock Exchange (SSE) from the years 2007-2010. The data used are secondary data and methods of data collection in this research is purposive sampling. In this method, Indonesia and China banking companies issuing annual report the year 2007-2010 and has acquired 16 Indonesia banking companies and 17 China banking companies from 31 Indonesia banking companies and 21 China banking companies. Data analysis methods used in this study is multiple regression analysis. Indonesia banking company dividend policy was only affected by ROE. Meanwhile, in China banking company dividend policy was only affected by Stock Price, Growth, and Operating Profit Margin. Keywords: Stock Price, Growth, Profitability, Free Cash Flow, Dividend Payout Ratio.